Fostering fraternity in humanity: the Church’s efforts to bring compassion within the framework of religious moderation - Dorlan Naibaho; Sandy Ariawan; Simion Diparuma Harianja; Jungjungan Simorangkir; Maringan Sinambela (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2022)
The nature of religion which refers to etymological studies clearly aims so that human life is not chaotic, so it is not surprising that all religions teach goodness. Only the lofty ideals of each religion cannot be adequately implemented among the grassroots so that it is presented precisely as violence and intolerance between adherents of one religion with another religion. Abuse in the name of religion occurs and becomes the beginning of the legitimacy of acts of violence in the cloak of religion. Reconciliation efforts are the church’s responsibility because the church has significant power in society and the church becomes a representation of God that brings the mandate and spirit of reconciliation to the world. The church is also the holder of the baton of Jesus' ministry on earth. In the historical reality of human life, Jesus is the only one who can do good and right throughout His life. The angel called him